2008
DOI: 10.1007/s11274-008-9899-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated cultivation of transgenic Bt cotton on functional bacterial populations in rhizosphere soil

Abstract: The impact of multiple-year (0-5 years) cultivation of transgenic Bacillus thuringiensis (Bt) cotton on the functional bacterial populations in rhizosphere soil was investigated. The transgenic Bt ? CpTI cotton line SGK321 and a non-Bt cotton line Shiyuan321 were planted in four fields in which Bt cotton had been continuously cultivated for 0, 1, 3, and 5 years. Rhizosphere soil samples were collected at the seedling, squaring, flower and boll, and boll-opening stages of cotton. Numbers of bacteria involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…Higher microbial populations in transgenic cotton grown soil were also reported by several workers (Shen et al 2006, Kapur et al 2010. Hu et al (2009) based on their multipleyear cultivation showed that transgenic Bt cotton was not found to affect the rhizosphere functional bacterial population. Saxena and Stotzky (2001) did not observe any significant differences in the numbers of culturable bacteria, actinomycetes, and fungi in the rhizosphere of transgenic Bt and non-transgenic maize.…”
Section: Resultssupporting
confidence: 63%
“…Higher microbial populations in transgenic cotton grown soil were also reported by several workers (Shen et al 2006, Kapur et al 2010. Hu et al (2009) based on their multipleyear cultivation showed that transgenic Bt cotton was not found to affect the rhizosphere functional bacterial population. Saxena and Stotzky (2001) did not observe any significant differences in the numbers of culturable bacteria, actinomycetes, and fungi in the rhizosphere of transgenic Bt and non-transgenic maize.…”
Section: Resultssupporting
confidence: 63%
“…In a study, Bt cotton producing cry protein had been cultivated for 5 years and the crop residues were incorporated into soil following post-harvest tillage. The authors concluded that multiple year cultivation of transgenic cotton may not affect the bacterial populations in soil (Hu et al 2009). Although Bt maize is the most studied GM crop, there is still a lack of continuity between studies at the laboratory and field scales.…”
Section: Effects Of Gm Plants On Soil Ecosystemsmentioning
confidence: 99%
“…Some studies have shown that repeated and large-scale use of transgenic Bt crops could lead to the accumulation and persistence of Bt proteins in soil [8,9,19,20]. Saxena and Stotzky (2002) showed that the toxin released in root exudates and from the biomass of Bt corn rapidly binds to surface-active particles in soil and remains larvicidal activity for at least 180 days [19,20,21]. The present study focused on the fertility status of Bt cotton soils compared with other crop cultivated soils in the region of Khammam, Andhra Pradesh, India.…”
Section: Introductionmentioning
confidence: 99%